Challenging Greed, Strengthening Gratitude: A Qur’anic Perspective on Modern Ecological Disasters in Sumatera - Gilang Malcom Habiebie; Siti Badi’ah; Budimansyah Budimansyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Ecological disasters occurring across Sumatera in recent years reveal that environmental degradation is not merely a natural phenomenon but is deeply intertwined with human moral and behavioral failures. This article examines how greed, excessive exploitation, and the neglect of ecological boundaries contribute to the intensification of floods, landslides, and ecosystem collapse. Using a qualitative descriptive approach, the study integrates Qur’anic teachings—particularly QS. Ar-Rūm:41 and QS. Ibrahim:7—with contemporary environmental analyses to examine the ethical foundations underpinning ecological sustainability. The Qur’an presents greed (ṭama‘) as a destructive inner disposition that leads to fasād (corruption) on earth, while emphasizing syukur (gratitude) and qana’ah (contentment) as virtues that guide humans toward responsible stewardship. The findings suggest that deforestation, illegal mining, river manipulation, and unregulated development in Sumatera align with Qur’anic descriptions of human-induced corruption, leading to ecological imbalance and increased disaster vulnerability. Furthermore, the study highlights that gratitude and contentment offer practical ethical principles that can inform sustainable environmental policies by promoting restraint, accountability, and alignment with ecological carrying capacity. The integration of Qur’anic values with scientific insights provides a holistic framework for addressing environmental crises, emphasizing the need for moral reform alongside technical solutions. Ultimately, the research highlights the importance of integrating Islamic ethical principles into environmental governance to foster equitable, sustainable, and spiritually grounded approaches to ecological preservation.